A study on infrared thermometer measurement capabilities in the calibration laboratories and the user community in Japan. Issue 1 (1st January 2021) - Yamada, Yoshiro; Kato, Tomonori; Shimizu, Takao; Ishii, Juntaro; Iguchi, Kouichi; Ishikawa, Kenji; Honjo, Hiroyuki; Ohsuga, Naohiro; Onda, Yoshinori; Suzuki, Kaori; Tsuda, Katsunori; Yamakawa, Takayuki; et al.
Abstract : A comparison circulating a standard infrared thermometer, a handy infrared thermometer, and a thermal imager was conducted among eleven participants from the industrial user, academic user, and calibration laboratory communities of these thermometers in Japan. The result revealed that the scatter width of the reported value for the handy type thermometer was as large as 31 °C at 450 °C. Investigation into the cause of the discrepancy showed that the treatment of emissivity of the source was one large factor, which is relevant when using contact thermometer or a near infrared radiation thermometer as the reference. Large SSE of the handy thermometer linked to the definition of the targeting distance of the thermometer on the blackbody cavity also played a major role. The comparison successfully identified the shortcomings of the current calibration practices, and the result can be utilized to greatly improve the reliability of the infrared thermometer scale in future.